Problematika Penguasaan Tanah oleh Warga Negara Asing dalam Usaha Pariwisata di Bali Perspektif Hukum Agraria Indonesia - Luh Gede Intania Purnami Putri Sukartha; Ni Ketut Sari Adnyani; I Wayan Lasmawan; Komang Febrinayanti Dantes (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the issue of land ownership by foreign nationals in the tourism industry in Bali from the perspective of Indonesian agrarian law. As an international tourism destination, Bali has experienced an increase in foreign investment, which has driven the development of tourism facilities and increased the demand for land. Law No. 5 of 1960 on the Basic Agrarian Principles (UUPA) adheres to the principle of nationality, which prohibits foreign nationals from holding title to land, stipulating that any transfer of rights to a foreign national is null and void. However, in practice, land ownership by foreign nationals through nominee agreements a form of legal circumvention is widespread. This phenomenon raises various issues, including rising land prices that make it difficult for local communities to retain their land ownership, the conversion of productive land that threatens environmental sustainability, and the dominance of foreign businesses that marginalizes local MSMEs. This study aims to analyze the legal framework governing land ownership by foreign nationals, identify the problems in Bali, and examine efforts to strike a balance between foreign investment and the protection of local communities. The study’s findings recommend strengthening oversight of nominee practices, revising licensing policies by raising the minimum investment threshold, and empowering local communities economically through equitable partnerships and strengthening the role of traditional villages.